Relationship between social media usage, self-efficacy, gender, and perceived social support among university students - Chen, Jessica Jing Yi; Tan, Yen Teng; Siau, Ching Sin (Penerbit Universiti Kebangsaan Malaysia, 2020)
Loneliness is an increasingly prevalent phenomenon globally. Psychological research has begun to focus on perceived social support as a solution to prevent or reverse the negative impacts of loneliness. Perceived social support, which is the feeling of being cared for by one’s social networks, could possibly be increased through usage of social media, especially in the IR 4.0 era. In addition to that, self-efficacy could contribute to one’s belief in the ability to form and maintain close relationships, and hence, it affects how much one feels supported by his/her social networks. The present study aims to determine the relationship between social media usage, self-efficacy, and perceived social support. The study also aims to identify any gender differences in terms of perceived social support. Data from 211 university students in Kuala Lumpur was analysed using Pearson’s correlation analysis and independent samples t-test. The findings show that there is a significant positive relationship between social media usage, self-efficacy, and perceived social support. Therefore, future interventions on social media usage and perceived social support should take into account the factors of self-efficacy, and social media could be utilised as an intervention to increase perceived social support.